Prolonged activated partial thromboplastin time in pediatric patients – an important diagnostic challenge - Zima, Aleksandra; Zdziarska, Joanna (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Basic hemostasis tests are among the most frequently performed laboratory investigations in pediatric practice. Therapeutic decisions regarding a child are often based on the results of screening hemostatic tests, such as the activated partial thromboplastin time (aPTT) or prothrombin time. Therefore, careful and accurate interpretation of these tests in the context of the specific patient, their clinical condition, and medical history is crucial for making the correct diagnosis. Although in most pediatric cases, aPTT prolongation is caused by pre-analytical errors, one must not overlook the possibility of underlying plasma coagulation disorders. In this article, we also highlight the relationship between the presence of mild plasma coagulation disorders and prolonged aPTT values.